Evaluating physical and biological characteristics of glutaraldehyde (GA) cross-linked nano-biocomposite bone scaffold - Hemabarathy Bharatham,; Siti Fathiah Masre,; Leo, Hwee Xien; Nurnadiah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In vivo stability of biomaterial-based bone scaffolds often present a significant drawback in the development of materials for tissue engineering purpose. Previously developed nanobiocomposite bone scaffold using alginate and nano cockle shell powder has shown ideal characteristics. However, it showed high degradation rate and reduced stability in an in vivo setting. In this study, we aim to observe the effect of cross-linking glutaraldehyde (GA) in three different concentrations of 0.5%, 1% and 2% during the fabrication process as a potential factor in increasing scaffold stability. Microstructure observations of scaffolds using scanning electron microscope (SEM) showed all scaffolds crossed linked with GA and control had an ideal pore size ranging from 166.8-203.5 μm. Increase in porosity compared to the control scaffolds was observed in scaffolds cross-linked with 2% GA which also presented better structural integrity as scored through semi-quantitative methods. Tested pH values during the degradation period showed that scaffolds from all groups remained within the range of 7.73-8.76. In vitro studies using osteoblast showed no significant changes in cell viability but a significant increase in ALP enzyme levels in scaffold cross-linked with 2% GA. The calcium content released from all scaffold showed significant differences within and between the groups. It can be concluded that the use of GA in the preparation stage of the scaffold did not affect the growth and proliferation of osteoblast and use of 2% GA showed improved scaffold structural integrity and porosity.